INOVASI BIOTEKNOLOGI UNTUK TERAPI PENYAKIT GENETIK - Loso Judijanto; Al-Amin (CV. ADIBA AISHA AMIRA, 2026)
Genetic diseases have long been a major challenge in the medical world, often difficult to treat with conventional methods. However, rapid developments in biotechnology have opened up new opportunities for more eflective therapies. The review in this study uses the literature method. The results showed that the latest biotechnology innovations applied in the therapy of genetic diseases can be done by gene therapy, genome editing using CRISPR-Cas9, stem cell therapy, and pharmacogenomic approaches. These techniques ofler the potential to repair or replace defective genes, regenerate aflected tissues, and optimise treatment based on an individual's genetic profile. With that, biotechnological innovations open a new era in the treatment of genetic diseases, oflering hope for patients and the potential to change the paradigm in the management of genetic conditions.